Within and between families: educational inequality in China - Zhang, S (2024)
This doctoral thesis systematically investigates the relationship between educational inequality in China and family background, exploring both between-family and within-family perspectives. It addresses key questions about the total effects of family background on education inequality over time, net birth order effects, and gender preferences in parental investment. Using sibling similarity for the first time in the Chinese context, Chapter 2 empirically examines family background effects and compares them across socioeconomic statuses and cohorts. Findings indicate a rise in educational inequality related to family background post-economic reform and education expansion. Although compulsory education and education expansion have positively affected equality, marketisation has amplified the effects of family capital on educational attainment. Chapter 3 controls for sibling-shared factors and gendered birth order structure using sibling fixed effects models and a newly designed gender-adjusted birth order index. It reveals that net birth order effects are negative after controlling for the macro trend of education expansion. It highlights the significance of macro-level factors in shaping within-family inequalities, as parental behaviours may be masked by societal transitions. Additionally, birth order effects present a gendered pattern with sons being preferred. Chapter 4 analyses gender preferences in parental investment in out-of-school education from two dimensions: sibling competition and family comparison. While females receive more in extracurricular courses in only-child families, analyses of multi-sibling families show that having brothers, especially younger brothers, negatively affects private tutoring investment for females. It further explores and discusses the potential reasons for gendered strategies based on stereotypes in economic return and cultural ideologies. The thesis provides unique insights into the impact of marketisation on educational inequality, the negative net effects of birth order, and the gendered dynamics of educational investment, offering a comprehensive understanding of educational inequality trends and contemporary Chinese family behaviours to inform policies ensuring educational equity.